1999
DOI: 10.1002/(sici)1096-9918(199908)27:8<743::aid-sia568>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Development of a standard method for quantitative depth profile analysis of zinc-based metallic coatings by direct current glow discharge optical emission spectroscopy

Abstract: A method for the determination of the thickness and composition of zinc‐based coatings on steel has been developed. The method is based on direct current glow discharge optical emission spectroscopy (GD‐OES). Six different types of coated materials supplied by five major European steel producers have been used to develop and evaluate the method. The types of coatings are hot‐dipped zinc, electroplated zinc, electroplated ZnNi, Galvanneal (electroplated and annealed ZnFe), Galfan (hot‐dipped Zn95Al5 alloy) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 6 publications
3
30
0
Order By: Relevance
“…The concept of constant emission yield (Y), defined as the emitted light per unit sputtered mass of an element, is commonly used for quantitative depth profile analysis of conducting coatings using dc-GD-OES [40,41] and successful results are obtained. However, it is known that Y sometimes depends on the plasma operating conditions (in one study it was concluded [42,43] that although the pressure, voltage, and current have some impact on Y, the emission yield is about four times more sensitive to changes in voltage or current than it is to changes in pressure).…”
Section: Radiofrequency Glow Discharge-optical Emission Spectrometrysupporting
confidence: 76%
“…The concept of constant emission yield (Y), defined as the emitted light per unit sputtered mass of an element, is commonly used for quantitative depth profile analysis of conducting coatings using dc-GD-OES [40,41] and successful results are obtained. However, it is known that Y sometimes depends on the plasma operating conditions (in one study it was concluded [42,43] that although the pressure, voltage, and current have some impact on Y, the emission yield is about four times more sensitive to changes in voltage or current than it is to changes in pressure).…”
Section: Radiofrequency Glow Discharge-optical Emission Spectrometrysupporting
confidence: 76%
“…1(a), the birth date of applied surface analysis can be determined fairly accurately by extrapolation of the curve depicting the number of publications with that keyword as a function of the publishing year, and is found to be 1970 (š1 year). Figure 1(b) shows the development of AES, 1,2 SIMS 3 and GDOES 4,5 in comparison. The developments of AES and SIMS are almost parallel but GDOES is obviously less frequently used and still far from saturation whereas both AES and SIMS are now mature techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Work in recent years has been very successful, providing a continually expanding range of applications for quantitative GD-OES . 6. Acknowledgements…”
Section: Developments In Near-surface Analysismentioning
confidence: 99%